2010
DOI: 10.3855/jidc.909
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and serovars of Salmonella from chickens and humans in Ibadan, Nigeria

Abstract: Background: This study determines the prevalence and antibiotic resistance of Salmonella serovars from humans and chickens in Ibadan, Nigeria, in 2004-2007. Methodology: A total of 991 blood samples were collected from patients in 2004 to 2005 and 641 fecal samples were collected from poultry farms in 2007. All Salmonella isolates were serotyped and tested for antimicrobial susceptibility. Results: Thirty-nine (4%) Salmonella isolates were obtained from human blood and 70 (11%) from chicken fecal samples. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
108
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 53 publications
(81 reference statements)
21
108
8
Order By: Relevance
“…In the current study, 33.3% of the isolates of Salmonella were resistant to TE, a finding considerably lower than the prevalence reported for isolates from similar sources in other countries (93 to 100.0%) (14,18,22). Table 3 shows the frequency of resistance patterns dis played, by country of origin.…”
Section: Resultscontrasting
confidence: 69%
“…In the current study, 33.3% of the isolates of Salmonella were resistant to TE, a finding considerably lower than the prevalence reported for isolates from similar sources in other countries (93 to 100.0%) (14,18,22). Table 3 shows the frequency of resistance patterns dis played, by country of origin.…”
Section: Resultscontrasting
confidence: 69%
“…Our findings indicated that qnrS was widely spread among poultry and their production environment in Nigeria. qnrS1 was recently found among Salmonella and E. coli from humans and animal sources in Nigeria [29,13].…”
Section: Discussionmentioning
confidence: 99%
“…Direct contact with infected animals may also cause Salmonella infections (Benenson et al, 1995;Tauxe, 1991). Although an increasing number of human salmonellosis cases have been linked to ingestion of contaminated vegetables and fruits, the most common route of infection is through food products derived from animals such as poultry and pigs (Braden, 2006;Fashae, Ogunsola, Aarestrup, & Hendriksen, 2010;. When the common serotypes from human infections are compared with those most commonly isolated from different animal sources, there are a number of instances of overlap (CDC, 2005).…”
Section: Introductionmentioning
confidence: 99%